Discharge to Rehabilitation Predicts Increased Morbidity in Patients Undergoing Posterior Cervical Decompression and Fusion. Issue 4 (6th May 2022) - Katz, Austen D.; Song, Junho; Ngan, Alex; Job, Alan; Morris, Matthew; Perfetti, Dean; Virk, Sohrab; Silber, Jeff; Essig, David
Abstract : Study Design: Retrospective cohort study. Objective: The aim was to compare 30-day readmission and postdischarge morbidity for posterior cervical decompression and fusion (PCDF) in patients who were discharged to home versus rehabilitation. Summary of Background Data: An increasing number of patients are being discharged to postacute inpatient care facilities following spine surgery. However, little research has been performed to evaluate the effect of this trend on short-term outcomes. Materials and Methods: Patients who underwent PCDF from 2011 to 2018 were identified using the National Surgical Quality Improvements Program (NSQIP)-database. Regression was utilized to compare primary outcomes between home and rehabilitation groups and to control for predictors of outcomes. Results: We identified 8912 patients. Unadjusted analysis revealed that rehabilitation-discharge patients had greater readmission (10.4% vs. 8.0%, P =0.002) and postdischarge morbidity (7.1% vs. 4.0%, P <0.001) rates. After controlling for patient-related factors, rehabilitation-discharge independently predicted postdischarge morbidity ( P <0.001, odds ratio=2.232). Readmission no longer differed between groups ( P =0.071, odds ratio=1.311). Rates of discharge to rehabilitation increased from 23.5% in 2011 to 25.3% in 2018, while postdischarge morbidity rates remained stagnant. Patients discharged to rehabilitation were older (66.9 vs. 59.4 y); more likely to be African American (21.4% vs. 13.8%) and have diabetes (27.1% vs. 17.5%), steroid use (6.4% vs. 4.7%, P =0.002), and American Society of Anaesthesiologists (ASA)-class ≥3 (80.2% vs. 57.7%); less likely to be male (53.9% vs. 57.4%, P =0.004) and smokers (20.3% vs. 26.6%); and had greater operative time (198 vs. 170 min) and length of hospital stay (5.9 vs. 3.3 d) ( P <0.001). Conclusions: Despite controlling for significant factors, discharge to rehabilitation independently predicted a 2.2 times increased odds of postdischarge morbidity. Rates of discharge to rehabilitation increased overtime without an appreciable decrease in postdischarge morbidity, suggesting that greater resources are being utilized in the postacute care period without an obvious justification. Therefore, home-discharge should be prioritized after hospitalization for PCDF when feasible. These findings are notable in light of reform efforts aimed at reducing costs while improving quality of care.